Handbook of research on ethics, entrepreneurship, and governance in higher education - Nair, Suja R. 1964-; Saiz Alvarez, Jose Manuel (IGI Global, 2019)
"This book focuses on the importance of ethics and application of ethics, entrepreneurship, and governance in higher education institutions. It also serves stakeholders of institutions imparting higher education design a code of ethics framework and governance policies that facilitate its implementation for the good of the society to foster entrepreneurship in their communities"--
Description based on title screen (IGI Global, viewed 08/22/2018)
Keywords: Education, Higher / Economic aspects; Education, Higher / Moral and ethical aspects; Academic-industrial collaboration; Business and education